University Students’ Perception of “Asistensi Mengajar” Program on Teaching Career : Persepsi Mahasiswa Terhadap Program "Asistensi Mengajar" untuk Karir Menjadi Guru - Setyowati, Lestari; Kurniawati, Linda (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2024)
The Asistensi Mengajar (AM) or Teaching Assistance designed to provide students with hands-on teaching experience in schools. Thus, it is preparing university students for future teaching careers. This research aims to assess the interest and readiness of students who participated in the AM program to become teachers after one semester of teaching experience. This research uses a survey research design with a quantitative approach and uses descriptive statistics for data analysis. The research population includes undergraduate English Language Education students of one of the state universities in Malang who have already joined AM during the 2022–2023 even semester, 2023–2024 odd semester, and 2023-2024 even semester; 46 students have participated in and finished the AM program and become the research sample. The result shows that students who participate in the AM program have an interest (32 respondents in the moderate category) and readiness (28 respondents in the high category) in becoming English teachers after graduating from university. The teaching profession remains a popular choice among undergraduate students, particularly in the English Language Education program. In conclusion, the AM program positively influences students' interest and readiness to pursue a teaching career post-graduation. Therefore, it is recommended that the university continue the AM program due to its beneficial impact on fostering students' interest and readiness to become teachers.